La descentralización territorial de los sistemas de garantía de rentas - Ayala Cañón, Luis (Cuadernos de Relaciones Laborales, 2006)
This paper considers to what extent the Spanish model of means-tested benefits causes regional inequalities in the coverage of low-income households. The Spanish model is often assumed to be a normal experience among the European Welfare States. This fact is put into question reviewing different schemes of decentralisation. Different empirical exercises are put into action to evaluate both the inequality effects of centralised benefits (non-contributory pensions) as well as those inequalities intrinsically linked to completely decentralised anti-poverty programs (regional minimum income programs). The empirical results show substantial inequalities raised by both institutional designs. It is necessary the search for a new model reducing the extreme design of the present systems.
Keywords: social assistance; poverty; decentralisation